The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.12968/jowc.2015.24.6.245
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan membranes in a rat model of full-thickness cutaneous wounds: healing and IL-4 levels

Abstract: According to our results chitosan membrane may promote early wound healing, reduce inflammation and affect the IL-4 pathway, however, the membrane degrades at the wound site after day 7.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Regarding the previous section, CS is a unique cationic biocompatible and biodegradable (see Section 5) polysaccharide that can be modified, as required, according to the needed end-use application. This is particularly true for biomedical and pharmaceutical applications ranging from drug delivery systems [164] to functional biomaterials [165], also considering tissue engineering [166], cell culturing [167], regenerative scaffolds [168], wound healing [169], smart hydrogels [170], active nanoparticles [171], anticoagulants [172], gene therapy [173], etc. (Figure 9).…”
Section: Biomedical and Pharmaceutical Functionsmentioning
confidence: 99%
“…Regarding the previous section, CS is a unique cationic biocompatible and biodegradable (see Section 5) polysaccharide that can be modified, as required, according to the needed end-use application. This is particularly true for biomedical and pharmaceutical applications ranging from drug delivery systems [164] to functional biomaterials [165], also considering tissue engineering [166], cell culturing [167], regenerative scaffolds [168], wound healing [169], smart hydrogels [170], active nanoparticles [171], anticoagulants [172], gene therapy [173], etc. (Figure 9).…”
Section: Biomedical and Pharmaceutical Functionsmentioning
confidence: 99%
“…In the present study, immunohistochemistry analysis demonstrated an increased the IL-4 for Ch compared with other experimental groups after 8 weeks, indicating that this treatment had the ability to attenuate the progression of OA. In addition, it was demonstrated that IL-4 is a chondroprotective agent which inhibits IL-1β and TNF-a synthesis (Nordback et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that mesenchymal stem cells promote wound healing in damaged skin [22,25]. It has also been shown that different products based on either collagen I or chitosan promote skin wound healing [26,27]. In addition, some reports have shown that regulation of the inflammatory response could be responsible for the regeneration/scar reparation balance [1].…”
Section: Hadmsc Are Viable In Collagen 1/chs/dexamethasonementioning
confidence: 99%